2019
DOI: 10.1080/17461391.2019.1621950
|View full text |Cite
|
Sign up to set email alerts
|

Are internal load measures associated with injuries in male adolescent Gaelic football players?

Abstract: This study aimed to examine internal loads in male adolescent Gaelic footballers and their association with musculoskeletal injury. Written training diaries were completed by 97 male adolescent Gaelic footballers weekly and injuries, defined as any injury sustained during training or competition causing restricted performance or time lost from play, were assessed by a Certified Athletic Therapist. Daily load was determined for each player (session rating of perceived exertion by session duration) and summed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Reducing pain caused by exertion and improving the perception of well-being lead to a decrease in specific risk of injury [32,33]. Thus, highlighted in this block is the need to:…”
Section: Relaxation-stretching and Rest Block (Rr)mentioning
confidence: 99%
“…Reducing pain caused by exertion and improving the perception of well-being lead to a decrease in specific risk of injury [32,33]. Thus, highlighted in this block is the need to:…”
Section: Relaxation-stretching and Rest Block (Rr)mentioning
confidence: 99%
“…Consistent with the observations made by coaches, the incidence of injury has been found to increase when training load increases suddenly in youth athletes from other sports. 12 This emphasises the importance of monitoring training load in gymnastics to reduce the risk of injury. 42 In line with previous research on injuries in youth gymnasts, growth-related injuries such as Osgood-Schlatter's disease, Sever's disease, osteochondritis dissecans and stress fractures of the wrist and back were frequently mentioned by coaches.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the observations made by coaches, the incidence of injury has been found to increase when training load increases suddenly in youth athletes from other sports. 12 This emphasises the importance of monitoring training load in gymnastics to reduce the risk of injury. 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training load has also been identified as a risk factor for injury in youth sport (Bowen et al, 2017;Dennis et al, 2005;Malisoux et al, 2013;Møller et al, 2017;Murray, 2017;Watson et al, 2017). Recent studies have found the risk of injury increases when there is a "spike" or an accumulation of high training loads (Bowen et al, 2017;Møller et al, 2017;O'keeffe et al, 2020;Watson et al, 2017). Currently, the training loads undertaken by youth trampoline gymnasts is unknown, and research regarding monitoring trampoline training load is limited (Gao et al, 2009;Van Der et al, 2007).…”
Section: Introductionmentioning
confidence: 99%